Bias resulting from missing information: some epidemiological findings. Issue 2 (June 1977) - Cox, A; Rutter, M; Yule, B; Quinton, D
Abstract : The biases resulting from missing information were examined in three psychiatric epidemiological studies. In each study, cases with missing information could be compared with the main sample because data were available from several sources or at several points in time through a longitudinal study. In almost all instances, cases with missing data differed systematically in terms of variables crucial to the questions being studied. In general, they tended to include a higher proportion with problems of various kinds--such as, behavioural deviance, reading backwardness, child or adult psychiatric disorder, and marital discord. The characteristics or circumstances of those giving information were generally more strongly associated with co-operation in testing or interviewing than the characteristics of those about whom information was sought. In some situations, the nature and degree of distortion resulting from missing information could lead to biased results.